2020
DOI: 10.1002/joc.6845
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spatial changes of extreme precipitation and temperature in Iran over a 50‐year period

Abstract: This research was carried out to determine whether the changes in precipitation and temperature trend in Iran are attributed to climate change or natural climate variability. The trend and its magnitude with the climatic extremes indices considered by Expert Team on Climate Change Detection and Indices were analysed based on the quality-controlled daily data of 37 meteorological stations by nonparametric Mann-Kendall test and Sen's slope method from 1966 to 2015. Results indicated that TXx, TNn, the average ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 58 publications
5
3
0
Order By: Relevance
“…At the other stations, a negative trend was recognized for the annual maximum 24-h precipitation (statistically significant at Kerman, Bandar Anzali, and Zahedan Stations), showing the lower levels of flash flood risk (Table 3). In this regard, our results are consistent with [38,57,58].…”
Section: Spatiotemporal Precipitation Trend By the Mann-kendall Testsupporting
confidence: 91%
“…At the other stations, a negative trend was recognized for the annual maximum 24-h precipitation (statistically significant at Kerman, Bandar Anzali, and Zahedan Stations), showing the lower levels of flash flood risk (Table 3). In this regard, our results are consistent with [38,57,58].…”
Section: Spatiotemporal Precipitation Trend By the Mann-kendall Testsupporting
confidence: 91%
“…In contrast, our results show that the total annual precipitation will decrease by 6.1% K-1 over Iran. While our results are generally consistent with the results of previous studies that have examined the precipitation change in Iran (Javari et al 2016;Khalili et al 2016;Daneshvar et al 2019;Alavinia and Zarei 2020;Sharafi and Mir Karim 2020;Doostan 2020;Sadeghinia et al 2022a), our findings provide a more detailed analysis of precipitation behavior in Iran, because we have examined changes in the characteristics (amount, frequency and intensity) of precipitation events of different intensities (light, moderate, heavy precipitation). The results in this paper indicate that dividing daily precipitation events into several categories is useful for a more detailed analysis of precipitation events.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…In general, a decreasing trend in precipitation has been observed in Iran (Khalili et al 2016;Javari et al 2016;Daneshvar et al 2019;Sharifi and Mir Karim 2020). Also, the number of wet days (RR) has decreased in most stations in Iran (Alavinia and Zarei 2020;Doostan 2020;Sadeghinia et al 2022a). It is important to ask whether the previous results regarding daily rainfall change patterns in Iran still hold according to additional observations; and the more important question is which of the types of precipitation events in Iran has changed significantly: light, moderate or heavy events?…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies (e.g., Modarres et al ., 2016; Alavinia and Zarei, 2020) showed that although the overall trend of precipitation has decreased, flood magnitude has increased in western and northwestern Iran. This trend is highly correlated with changes in Mediterranean and Sudanese cyclone intensity (Khoshakhlagh et al ., 2008; Sabziparvar et al ., 2010; Heydari and Khoshakhlag, 2015; Bayat et al ., 2017; Kiani et al ., 2020; Rezaei et al ., 2021; Sherpa and Shirzaei, 2022).…”
Section: Study Areamentioning
confidence: 99%